A checklist and floristic summary of the vascular plants of Napa County, California - Crain, Benjamin J.; White, Jeffrey W. (Phytotaxa, 2013)
Napa County contains particularly high levels of biological diversity in a variety of categories and is considered one of ten localized areas in California that contain the highest numbers of native and endemic plant species. Here we present a floristic summary based on a new annotated checklist of the flora of this uniquely diverse region. The checklist was developed by combining several local and statewide floristic data sources that represent herbarium collection records and other observations from Napa County. The final checklist of vascular plants for Napa County consists of 1,716 taxa, including 1,418 native taxa from 101 different families. Alarmingly, 126 native taxa in Napa County were listed as rare or threatened to some degree. The results of this study demonstrate that for its size, Napa County contains remarkably high levels of plant diversity as well as high concentrations of special status taxa as compared to other areas within the California Floristic Province, the State of California as a whole, and other regions within global biodiversity hotspots characterized by Mediterranean climates. In particular, this analysis highlights the floristic significance of Napa County at global and local levels, and thus, this review is an important step to help promote and facilitate long term research and conservation planning in the area.